No Correlation between Self-Directed Learning and Life Skills: How to Explain? - Yanti, Indah; Antika, Linda Tri (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2023)
21st-century education demands students to possess learning and innovation skills, proficiency in using technology, information media literacy, and life skills. This research aims to determine the correlation between students' self-directed learning and life skills. The subjects of this study were XF class students, totalling 32 students. Self-directed learning was measured using a questionnaire, including students' interest in learning biology, self-efficacy, self-assessment, and self-reaction. Meanwhile, life skills were measured using an observation sheet covering interpersonal skills, goal setting and collaborative achievement, responsibility, and management. Learning was conducted by implementing guided inquiry-based learning. This research is a correlational study using regression correlation through the SPSS program. The results of this study indicate no correlation between self-directed learning and students' life skills. Guided inquiry remains a reference in efforts to empower self-directed learning and life skills.